Responsiveness of children with celiac disease to different hepatitis B vaccination protocols - Necati BALAMTEKİN; Nuray USLU; Gökhan BAYSOY; İnci SALTIK-TEMİZEL; Hülya DEMİR; Aysel YÜCE (Turkish Journal of Gastroenterology, 2019)
-